(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This scientific article is devoted to the analysis of the results of monitoring conducted on agricultural lands. The problems identified during the monitoring, ways to eliminate them and recommendations for the rational use of land in the future are outlined. The results of the study are important in shaping state policy in the field of agriculture and developing regional development programs. The study examined the shortcomings of existing monitoring methods and assessed the feasibility of obtaining high-resolution data using drones and satellite imagery. A 22-hectare experiment demonstrated that drones provide information with 90-95% accuracy, but are difficult to implement over large areas. Satellite monitoring, meanwhile, offers 80-90% accuracy and covers large areas in a short time. Based on this, the cost effectiveness, time consumption, and resource efficiency of both methods are compared.